Islamic Psychotherapy Model to Overcome Fear: Study of The Novel Hati Suhita by Khilma Anis - Nisrina Qatrunnada; Marwan Hayeemaming (Journal of Sufism and Psychotherapy, 2024)
Islamic psychotherapy is an effort to overcome psychological problems based on Islamic religious views (Al-Quran and Hadith). Islamic psychotherapy explains how the practice of Islamic psychotherapy can overcome psychological disorders in the form of fear and other psychological disorders. Islamic psychotherapy with its religious and spiritual values will calm individuals from psychological disorders in the form of fear. This research is a library research, which is a research that uses books as the main source. While the approach in this research is a qualitative approach. The data collection technique uses the simak catat method. The data is analyzed by content analysis. The formal object in this research is Islamic psychotherapy and fear, while the material object is the novel Hati Suhita. The results of this study concluded that: 1) The fear of the main character in the novel Hati Suhita by Khilma Anis is the fear of household destruction, because the husband still loves the woman in the past. The fear is characterized by physical, behavioral and cognitive symptoms. Physical symptoms are characterized by anxiety, trembling, palpitations, weakness, and difficulty breathing. Behavioral symptoms include avoidance behavior. And cognitive symptoms are characterized by worrying about something, feeling disturbed about future fears, and fear of inability to overcome problems. 2) The Islamic psychotherapy model in the novel Hati Suhita by Khilma Anis is in the form of prayer, tadarus Al-Qur'an, pilgrimage to the grave of the guardian, and prayer. From some of these Islamic psychotherapies, it can reduce the fear experienced by the main character and end up not being afraid at all. It is characterized by happy, calm, fresh, stable and positive thinking.